THE CULTURE INFLUENCE IN TEACHING AND LEARNING LANGUAGE IN EFL CLASSES - Fazliddinova, Zulfiyakhon Dilmurod qizi (Educational Research in Universal Sciences, 2023)
Culture has wider meaning than we understand, nowadays. Teaching new langauge without its cultural rules and competences may cause a great many problems in communication and misunerstanding in learning their language, as language itself reflects the natives culture totally. So, this article focuses in the problems and solutions, how cultural awareness, and cultural phenomenon reflect on the new EFL language learner.